ANALYSIS OF THE DEPENDENCES OF THE PARAMETERS OF TRANSISTOR ANALOGUES OF INDUCTANCE ON TEMPERATURE - OSADCHUK, OLEXANDER; DUMENKO, DENYS (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article analyzes the dependence of parameters of transistor analogs of inductance (TAI) on temperature. The effect of temperature on the elements of the first group is considered. The effect of temperature on the parameters of the electrical model of the transistor is considered. The main formulas that can be used in practical calculations to determine the emitter resistance in the temperature range of transistor application from -160 to 160 degrees Celsius have been determined. The dependence of the capacitance of the emitter junction in the temperature range from -70 to 70 degrees Celsius is determined, and the corresponding formulas for its calculation are given. The dependence of the resistance of the transistor base on the temperature was studied separately for silicon and silicon-germanium transistor structures, and the corresponding expressions of the dependences were given. The temperature dependence of the value of the collector junction capacitance of the transistor structure was analyzed, and its dependences were determined for both silicon and silicon-germanium transistors. The dependence is derived, which is valid at a temperature from 0 to 80 degrees Celsius. The studied current transfer coefficient and its dependence on temperature, corresponding calculations are given, which prove this dependence, which is valid at a temperature from -70 to 70 degrees Celsius. The dependence of the limiting frequency of transistor operation on temperature was also investigated, the correcting coefficients for drift and driftless transistors were derived, the corresponding calculations and formulas were given. Graphs of dependences of emitter junction resistance and base resistance on temperature are given. For all investigated parameters of the transistor structure, the main temperature ranges are derived, which will be valid when applied within the specified limits. Conclusions have been made about the appropriate possibilities of application when the temperature increases or decreases, and the necessary actions to preserve the effective use of transistor structures in such conditions.
Keywords: parameters; temperature; transistor; inductance; frequency; current; emitter; collector; base; goodness; load; silicon; range